2011
DOI: 10.3109/14767058.2010.547961
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral blood flow autoregulation and congenital heart disease: possible causes of abnormal prenatal neurologic development

Abstract: Cerebrovascular resistance is significantly lower in fetuses with CHD, especially in cases of left side obstruction. The cerebro/placental hemodynamic changes are similar to that described in fetuses with placental insufficiency and may contribute to their abnormal neurologic development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
65
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(72 citation statements)
references
References 23 publications
5
65
2
Order By: Relevance
“…No other subtypes were associated with disproportionately smaller head circumference, as previously suggested in other studies of TOF, HLHS, or aortic arch hypoplasia. 13,15,20,[41][42][43] We found disproportionately larger head circumferences relative to birth weight in major VSDs and other less severe subtypes of CHD. No previous studies have reported such associations.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…No other subtypes were associated with disproportionately smaller head circumference, as previously suggested in other studies of TOF, HLHS, or aortic arch hypoplasia. 13,15,20,[41][42][43] We found disproportionately larger head circumferences relative to birth weight in major VSDs and other less severe subtypes of CHD. No previous studies have reported such associations.…”
Section: Discussionmentioning
confidence: 84%
“…Ultrasound studies have demonstrated brain sparing in fetuses with CHD, 13,16,17,19,42,43 and MRI studies have demonstrated decreased fetal cerebral volume before birth. 7,14 Recently, measures of fetal cerebral oxygenation were directly linked to prenatal brain volume.…”
Section: Discussionmentioning
confidence: 99%
“…Donofrio et al (20) were the first to report reduced head circumference (HC) measurements in fetuses with CHDs in the third trimester. Similarly, Arduini et al (21) found lower HC at 34 weeks' gestation. Masoller et al (22) documented, for the first time, that a remarkable fraction of fetuses with CHD already have biparietal diameter (BPD) and HC values below the 5th percentile (50% and 25%, respectively) for expected gestational age in the second trimester of pregnancy.…”
Section: Editorialmentioning
confidence: 97%
“…Ruiz et al (27) have found that fetuses with CHDs presented a small head at ultrasound diagnosis (BPD −1.32±0.99 Zs, HC −0.79±1.02 Zs), which remained small throughout gestation, a finding that was confirmed at birth (HC Zs −0.56±1. 21 CHDs presented an MCA and CPR below the 5th centile at the time of first examination. UtA and UA Doppler ultrasound parameters showed a significant increase towards the end of pregnancy, whereas no significant changes were observed for MCA or CPR with advancing gestational age.…”
Section: Editorialmentioning
confidence: 99%
“…Antenatally, normal distribution of oxygenated blood could be disturbed and vascular resistance may be altered in fetuses with CHD [3,6,7,8]. It has been reported that fetuses with left-sided obstructive lesions (LSOL) have lower pulsatility indices of the middle cerebral artery (MCA-PI) compared with fetuses without CHD [9].…”
Section: Introductionmentioning
confidence: 99%